Polypharmacy among older adults in Brazil: Association with sociodemographic factors and access to health services - Karina Alves Ramos; Alexandra Crispim Boing; Juliana Mara Andrade; Fabíola Bof de Andrade (Elsevier, 2022)
Background: Polypharmacy is common among older adults and is of public health concern, since pharmacological therapy influences the quality of care for older individuals. Few studies have addressed its prevalence and correlates in low or middle-income countries. Objective: To evaluate the prevalence of polypharmacy in a representative sample of the Brazilian older population and its association with sociodemographic conditions and factors related to access to health services. Methods: Cross-sectional study with data from the last National Health Survey, conducted in 2019. The dependent variable was polypharmacy (five or more medications) and independent variables were: sociodemographic characteristics, general health conditions and access to health services indicator. Results: The prevalence of polypharmacy was 19.2%. Polypharmacy was higher among those aged 80 years and over compared to those aged 60-69 years (prevalence ratio (PR) 1.47; 95% CI: 1.30; 1.66); individuals with complete elementary education (PR 1.35; 95% CI: 1.13; 1.60) versus those who did not go to school; with 3+ chronic diseases (PR 11.14; 95% CI: 7.94; 15.63); those with limitations in basic activities of daily life (PR 1.49; 95% CI: 1.35; 1.63) and possession of private medical health insurance (PR 1.32; 95% CI 1.19; 1.46). Being in a marital relationship was inversely associated with polypharmacy (PR 0.88; 95% CI: 0.80; 0.96). Conclusion: Polypharmacy affects a significant proportion of the Brazilian older population and is associated with sociodemographic factors and access to health services.